Design and development of a new electromagnetic prime mover using solenoid technology: Solenoid Powered Engine model simulation (torque vs. speed characteristic) - Bahrin S.Z.A.S.K.; Amirulddin U.A.U. (Institute of Electrical and Electronics Engineers Inc., 2023)
The Solenoid Powered Engine (SPE) is one of the feasible alternative prime movers to replace the existing electric motors. From the machine's design and operational perspective, this particular prime mover design holds a few advantages over the existing electric motor designs. However, SPE development is still in its infant stages and future studies and improvements are required to further refine the SPE wide potential. Therefore, the authors have developed a simulation template model to identify the machine's terminal characteristic. The simulation template model is based on the machine's power flow and mechanical linkages or operations. As a result, the authors managed to create a simulation model for the machine and also introduced the SPE terminal characteristic, which is similar to a DC series motor. The simulation model can be used to simulate various SPE designs for future developments. This paper basically describes the SPE simulation design, torque vs. speed characteristic and analysis. © 2014 IEEE.